Crossover Evaluation of Silicone Hydrogel Daily Disposable Contact Lenses. Issue 11 (November 2015) - Wolffsohn, James S.; Mroczkowska, Stephanie; Hunt, Olivia A.; Bilkhu, Paramdeep; Drew, Tom; Sheppard, Amy
ABSTRACT: Purpose: To assess the surface tear breakup time and clinical performance of three daily disposable silicone hydrogel contact lenses over 16 hours of wear. Methods: Thirty-nine patients (mean [±SD] age, 22.1 [±3.5] years) bilaterally wore (narafilcon A, filcon II-3, and delefilcon A) contact lenses in a prospective, randomized, masked, 1-week crossover clinical trial. Tear film was assessed by the tear meniscus height (TMH), ocular/contact lens surface temperature dynamics, and lens surface noninvasive breakup time at 8, 12, and 16 hours of wear. Clinical performance and ocular physiology were assessed by subjective questionnaire, by high-/low-contrast logMAR (logarithm of the minimum angle of resolution) acuity, and through bulbar and limbal hyperemia grading. Corneal and conjunctival staining were assessed after lens removal. Results: Delefilcon A demonstrated a longer noninvasive breakup time (13.4 [±4.4] seconds) than filcon II-3 (11.6 [±3.7] seconds; p < 0.001) and narafilcon A (12.3 [±3.7] seconds; p < 0.001). A greater TMH (0.35 [±0.11] mm) was shown by delefilcon A than filcon II-3 (0.32 [±0.10] seconds; p = 0.016). Delefilcon A showed less corneal staining after 16 hours of lens wear (0.7 [±0.6] Efron grade) than filcon II-3 (1.1 [±0.7]; p < 0.001) and narafilcon A (0.9 [±0.7]; p = 0.031). Time was not a significant factor for prelens tear film stability (F = 0.594, p = 0.555) or TMH (F = 0.632, p = 0.534). Lens brand did not affect temperature (F = 1.220, p = 0.308), but it decreased toward the end of the day (F = 19.497, p < 0.001). Comfort, quality of vision, visual acuity and contrast acuity, and limbal grading were similar between the lens brands but decreased with time during the day (p < 0.05). Conclusions: The tear breakup time over the contact lens surface differed between lens types and may have a role in protecting the ocular surface.